Analysis of Road Preservation Priority Criteria Based on the Provincial/Kabupaten Road Management System (PKRMS) on the Arjosari–Purwantoro Road Section, Pacitan Regency - Hanggana Prayuda Bakti; Hanie Teki Tjendani; Esti Wulandari (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Road infrastructure plays a strategic role in supporting community mobility, the distribution of goods and services, and regional economic development. However, limited regional budgets require local governments to establish preservation priorities systematically to ensure effective and efficient resource allocation. The Provincial/Kabupaten Road Management System (PKRMS) provides comprehensive technical data on road conditions, yet technical data alone are insufficient for determining preservation priorities when multiple road segments compete for limited funding. This study aims to analyze the criteria influencing road preservation priorities based on PKRMS data for the Arjosari–Purwantoro Road Section in Pacitan Regency. The criteria analyzed include pavement condition, traffic volume, road function, regional connectivity, socio-economic benefits, accessibility to public facilities, and estimated maintenance costs. The Analytical Hierarchy Process (AHP) was employed to determine the relative importance of each criterion through pairwise comparisons, producing a prioritized ranking that supports objective decision-making. The integration of PKRMS and AHP provides a structured framework for evaluating road segments based on both technical and strategic considerations. The results of this study are expected to identify the most influential criteria in determining road preservation priorities and to provide a rational basis for prioritizing preservation programs on the Arjosari–Purwantoro Road Section. Furthermore, the proposed approach is expected to assist local governments in developing road preservation plans that are effective, efficient, transparent, and accountable, while maximizing the socio-economic benefits of limited infrastructure investment.